THE ROLE OF CREATIVE WRITERS IN THE INTEGRATION OF THE CULTURAL FIELD IN THE NEW UZBEKISTAN - Uktamovich, Bokiyev Baxrom (Journal of Learning on History and Social Sciences, 2024)
Objective: This article investigates the contributions of creative intellectuals in Uzbekistan during the years of independence, focusing on their work in higher education, historical research, and responses to globalization challenges. Methods: Using a qualitative approach, this study examines policy transformations, intellectual achievements, and institutional reforms in education, emphasizing the shift from authoritarian ideologies to democratic principles. Results: Findings reveal that educational and cultural reforms in Uzbekistan have fostered an environment supportive of intellectual freedom, where state institutions increasingly prioritize public service and human development. Additionally, creative intellectuals’ involvement in international collaborations has expanded, leading to greater cultural exchange and global visibility. Novelty: This study highlights the significant departure from Soviet-influenced historiography toward an objective, historically accurate framework for understanding Uzbekistan’s past. Educational materials, now free from ideological biases, have become tools for nurturing well-rounded individuals, reflecting Uzbekistan's progress in establishing a democratic, citizen-focused state.